1988
DOI: 10.2337/diab.37.5.653
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance by Uncleaved Insulin Proreceptor: Emergence of Binding Site by Trypsin

Abstract: Two sisters presented with severe insulin resistance and markedly decreased insulin binding to erythrocytes, cultured fibroblasts, and transformed lymphocytes. The dose-response curve of insulinstimulated amino acid uptake in the fibroblasts was shifted to the right. The molecular weight of the insulin receptor on the transformed lymphocytes from the patients was 210,000 and could not be dissociated to a-and p-subunits by dithiothreitol treatment. However, the proreceptor was cleaved by trypsin, and this led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
10
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 18 publications
3
10
0
Order By: Relevance
“…In addition, mutational analysis has provided insights into the functional roles of specific structural domains in the receptors. In some patients, mutations have been described that impair posttranslational processing and transport of receptors to the plasma membrane (4)(5)(6)(7) or alter the affinity with which the receptor binds its ligand (6)(7)(8)(9). Furthermore, mutations have been described that interfere with other functions of the receptor such as receptor-mediated endocytosis and delivery of low density lipoprotein for utilization within the cell (10) or transmembrane signaling by inactivating the insulin receptor tyrosine kinase activity (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…In addition, mutational analysis has provided insights into the functional roles of specific structural domains in the receptors. In some patients, mutations have been described that impair posttranslational processing and transport of receptors to the plasma membrane (4)(5)(6)(7) or alter the affinity with which the receptor binds its ligand (6)(7)(8)(9). Furthermore, mutations have been described that interfere with other functions of the receptor such as receptor-mediated endocytosis and delivery of low density lipoprotein for utilization within the cell (10) or transmembrane signaling by inactivating the insulin receptor tyrosine kinase activity (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…The ␣ and ␤ subunits are synthesized as a single precursor polypeptide (proIR) that is cleaved after being transported to the Golgi compartments (2) on the carboxyl side of the tetrabasic amino acid sequence (Arg-LysArg-Arg 735 ) located at the junction between the two subunits (3,4). The physiological importance of proteolytic proIR maturation was demonstrated in patients who were suffering major insulin-resistant diabetes because of an Arg 735 3 Ser substitution at the proIR processing site (5,6). Moreover, a processing defect in the proIR was observed in the livers of a particular animal model for diabetes (7).…”
Section: Gaining the Full Activity Of The Insulin Receptor (Ir) Requimentioning
confidence: 99%
“…The mature insulin receptor (IR) 5 is a heterotetrameric transmembrane protein composed of two disulfide-linked dimmers, each of which has an amino-terminal ligand-binding ␣ subunit and a carboxyl-terminal tyrosine kinase active ␤ subunit (for review, see Ref. 1).…”
Section: Gaining the Full Activity Of The Insulin Receptor (Ir) Requimentioning
confidence: 99%
“…Thus, a primary defect in insulin receptors leads to extreme insulin resistance as demonstrated in type A insulin resistance [3][4][5][6][7][8][9][10][11][12][13][14], leprechaunism [4,6,7,11,[14][15][16][17][18][19][20][21][22][23][24], and Rabson-Mendenhall syndrome [14,[25][26][27]. Recently, we [28,29] and Kakehi et al [30] reported a patient with type A extreme insulin resistance due to abnormal processing of the insulin proreceptor. Subsequently, DNA sequencing of the interconnecting region between alpha-and beta-subunits revealed G-+T point mutation which changed -Arg-Lys-Arg-Argto -Arg-Lys-Arg-Ser- [31,32].…”
mentioning
confidence: 99%
“…The Arg---+Ser structural change appeared to be the cause for abnormal processing of the insulin proreceptor. However, attention has been focused on the mechanism of abnormal processing of the proreceptor in the previous studies [28][29][30][31][32], and functional properties of the unprocessed insulin proreceptor itself have not been investigated in detail. Since insulin binding was markedly decreased, hormone binding specificity and intramolecular signal transmission may also undergo a change by structural alteration due to abnormal processing of the insulin proreceptor.…”
mentioning
confidence: 99%